Learning Creativity and Student's Performance: An Empirical Study From Portugal - Gonçalves, Cátia; Rua, Orlando Lima (E- Revista de Estudos Interculturais, 2021)
This research aims to recognize the influence that creativity units/modules/seminars has on academic performance of students who attend. Consequently, the purpose of this study is to understand the impact that learning creativity has on Porto Accounting and Business School (ISCAP) students’. Therefore, a quantitative methodology was developed through a questionnaire with 240 answers from ISCAP’s students. The data was studied through reliability and explanatory factorial analysis in order to find the relation between the physical environment, learning climate and learner engagement on the performance of students. The results show that the physical environment and learning climate have a positive influence on students’ performance but the same does not happen with the motivation of students. These findings focus on the necessity to improve the students’ engagement. It is recommended that ISCAP will take into account the factors that lead to the referred results so as to reform and develop new ways in which to improve students’ performance through students’ motivation.